The feasibility of using fly ash from power plants in improving the physical and mechanical properties of clay and Silty clay. - حنا, رامي (Latakia University Journal -Engineering Sciences Series, 2023)
Road construction requires certain types of soils that must meet specific specifications that are sometimes difficult to secure, especially near the construction area. Therefore, the cost of construction increases significantly, except for the inability to use geotechnically and geometrically weak excavation materials in backfilling, which are later replaced with good materials suitable as foundation materials for road paving layers. . Therefore, the researchers resorted to the possibility of using the excavation outputs as new construction materials after treating them with additives such as cement, quick or slaked lime, and appropriate chemical additives. Later, fly ash appeared from power plants as an effective material for soil stabilization, especially at the end of the last century, as it gave good results, especially when stabilizing and strengthening the soil under the paving layers, and even as a new material (soil + fly ash that can be used in the paving layers). In our research, it was successfully tested. Improving the weak soil from two sites in Lattakia city by adding fly ash from the power generation station in Banias, so the C.B.R bearing capacity properties of the first soil improved by an amount of 125% when adding a percentage of ash that reached 15% of the weight of the soil, and for the second soil by 215% at the same percentage from the ashes.